Rapid in situ formation of a double cross-linked network hydrogels for wound healing promotion - Liu, Yifan; Zhang, Ye; Jia, Qianqian; Liang, Xiaoyun; Xu, Kejin (Frontiers in Pharmacology, 2025)
The persistent challenge lies in accelerating wound healing. Bioactive hydrogels with in situ formation properties ensure that the dressing completely adheres to the wound and isolates it from external bacteria and microorganisms in order to meet the needs of damaged skin tissue for rapid hemostasis and wound healing. In this paper, hydrogel dressing that Polyacrylamide/Sodium alginate grafted with dopamine/Gelatin grafted with glycidyl methacrylate doped with Angelica sinensis polysaccharide was prepared (PDGA). Chemical cross-linking of PAAM by adding cross-linking agent to initiate free radical polymerization and photocross-linking by free radical polymerization of GMA-GEL under UV light irradiation are two cross-linking modes to construct dual-cross-linking network of PDGA hydrogel dressing. The hydrogel remains fluid when placed in a sealed syringe and solidify rapidly by photocross-linking when placed on the wound. Furthermore, the hydrogel demonstrated excellent biocompatibility and hematological safety. The interaction between angelica polysaccharides and integrins on the platelet surface facilitated an augmentation in platelet adhesion, activation, and aggregation, ultimately inducing rapid coagulation of the blood within 130 s in a mouse tail vein hemorrhage model. ASP can promote tissue healing by promoting cell proliferation around wounds and accelerating the formation of new blood vessels. In a mouse skin defect model, collagen deposition, blood vessel formation, hair follicle regeneration, and granulation tissue formation were observed due to the presence of angelica polysaccharides, showing significantly superior wound healing properties when compared to Tegaderm™ film. In addition, the expression of CD31 in skin wounds treated with PDGA was significantly upregulated. Consequently, PDGA multifunctional dressings exhibit considerable potential for in vitro hemostasis and skin wound repair applications.